Relevance Of Soil Testing To Agriculture And The Environment - Kamprath, Eugene J.; Beegle, Douglas B.; Fixen, Paul E.; Hodges, Steven C.; Joern, Brad C.; Mallarino, Antonio P.; Miller, Robert O.; Sims, J. Thomas; Ward, Raymond; Wolf, Ann M. (Council for Agricultural Science and Technology (CAST), 2000)
This issue paper helps pinpoint factors that need to be considered as farmers and others use soil tests as a guide to protecting the environment while producing economical food. The issue paper provides perspective on the increasingly important role of soil tests, which farmers have long used in making crop production decisions.